“OPTIMASI JARINGAN PADA PANGKALAN UDARA DI INDONESIA MENGGUNAKAN METODE MINIMUM SPANNING TREE” - Suwardi, Arie Prasetya; Mufti Arifin; Endah Yuniarti (Jurnal Teknologi Kedirgantaraan, 2024)
Air Force Bases (Lanud) in Indonesia have a crucial role in maintaining national security and defense, especially in supporting the operations of the Indonesian Air Force. This study aims to find the Minimum Spanning Tree network between Air Force Bases (Lanud) in Indonesia using the Minimum Spanning Tree (MST) method. Minimum Spanning Tree (MST) is used to connect all Lanud. By using the Minimal Spanning Tree Method analysis, it can provide an optimal solution by producing a minimum total travel distance with a direct connection procedure at the points (nodes) on a network. Contributing positively to operational activity planning, more effective use of resources, and rapid response in emergency situations. The data used in this study are secondary data, namely data on the distance between 44 Lanud in Indonesia obtained from Google Earth. This data uses nautical miles units. The data obtained is represented in the form of a matrix and graph, then the parameters used are determined. After that, the data is analyzed using a minimum spanning tree. The results of the Minimum Spanning Tree analysis show that the optimum network connecting 44 Air Force Bases has a total distance of 6664 NM, which increases the efficiency, readiness, and flexibility of the TNI AU's operational planning in responding to emergency situations by each air force base optimally. Most TNI AU aircraft are able to travel the minimum spanning tree network with the longest distance from Halu Oleo Air Force Base to El Tari Air Force Base of 371 NM, except for the SA-330 Puma aircraft which can only travel 300 NM.